Digital tax policies and compliance challenges for MSMEs in Indonesia - Sibarani, Pasu; Fadjarenie, Agustin; Widayati, Catur; Tarmidi, Deden (Edelweiss Applied Science and Technology, 2024)
As digital Micro, Small, and Medium Enterprises (MSMEs) rapidly grow in Indonesia, ensuring their compliance with tax regulations has become an urgent priority. This study delves into the challenges and innovative solutions to enhance tax compliance, focusing mainly on digital content creators. This study examines the challenges and solutions for improving tax compliance among digital Micro, Small, and Medium Enterprises (MSMEs) in Indonesia, mainly digital content creators. The research aims to analyze the impact of tax sanctions, modernization of tax administration, and tax policy reforms on the compliance behavior of these entities. A qualitative approach was employed, utilizing interviews and focus group discussions (FGDs) with informants selected through purposive sampling. The findings indicate that tax sanctions significantly influence compliance, but modernization of tax systems improves transparency and efficiency, thus enhancing compliance. Policy reforms, particularly those tailored to the unique needs of digital businesses, offer the flexibility needed for fulfilling tax obligations. The novelty of this research lies in the proposed model that integrates tax sanctions, administrative modernization, and policy reforms, addressing the unique characteristics of digital MSMEs. The practical implications suggest that implementing a user-friendly digital tax system, supported by clear guidelines and targeted reforms, can simplify compliance for digital MSMEs, leading to better tax reporting. These findings provide actionable insights for policymakers in designing effective, adaptive tax policies for Indonesia’s rapidly growing digital economy.